Reflections on the supervised relationship and interaction in nursing clinical training - Rocha, Inês Alves da Rocha e Silva; Carvalho, António Luís Rodrigues Faria de (Rev Rene, 2013)
This reflection fits into the area of Clinical Supervision in Nursing focusing on relationships that the student develops during clinical training. It seems that in clinical training the student not only learns but also consolidates verbal, procedural and attitudinal contents. The relationship established with peers, teachers and tutors will contribute to their professional identity. It is underlined the importance of the contribution of clinical supervision for the development of a reflective thinking in students in Portugal, as highlighted here, which influences the changes in nursing practices, as well as ensuring the quality and safety of the care provided. The characteristics that the tutor must have to improve the development of the students are also explained as well as the possible solutions for the existing limitations of clinical training contexts. DOI:https://doi.org/10.15253/2175-6783.20130002000021